National affiliation: An Anthropological vision about the loss of national identity - Nasser, Muhammad Baqir; Salman, Hussain Fadel (Al-Adab Journal, 2020)
The sub-identities could undermine the connection between people, that happens if there is no short and long term strategic plans, so the connection is the best way to create loyalty to the country.Some countries fear the substance of sub-identities, Europe communities suffered of appearance of daesh, so we tied that to Iraqi situation with mentioning the history.